2020
DOI: 10.1155/2020/6672386
|View full text |Cite
|
Sign up to set email alerts
|

Coevolutionary Dynamics of Organic-Inorganic Interactions, Hydrocarbon Generation, and Shale Gas Reservoir Preservation: A Case Study from the Upper Ordovician Wufeng and Lower Silurian Longmaxi Formations, Fuling Shale Gas Field, Eastern Sichuan Basin

Abstract: Shale gas deposits are self-sourced, self-accumulating, and self-preserving in the Upper Ordovician Wufeng Formation and Lower Silurian Longmaxi Formation of the Fuling Shale Gas Field in the eastern Sichuan Basin. They were both seemingly mixed by secondary oil cracking and kerogen cracking gases during the high maturation window. The reservoir space primarily consists of mineral pores and organic matter (OM) pores, and the shale gas was mainly trapped by a high-pressure system. In this study, the Fuling O3w-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The Wufeng Formation–Longmaxi Formation shale gas field caprock includes direct and indirect (regional) caprocks. The direct caprock consists of the middle and upper Longmaxi Formation shales (above the LM5 graptolite shale zone), with low porosity, relatively high breakthrough pressure, and no plastic deformations and fractures . The caprock overlying the shales in the Wufeng Formation and lower Longmaxi Formation (WF2-LM4 graptolite shale zones) has a strong sealing efficiency .…”
Section: Characteristics Of Overpressured and Normally Pressured Shal...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Wufeng Formation–Longmaxi Formation shale gas field caprock includes direct and indirect (regional) caprocks. The direct caprock consists of the middle and upper Longmaxi Formation shales (above the LM5 graptolite shale zone), with low porosity, relatively high breakthrough pressure, and no plastic deformations and fractures . The caprock overlying the shales in the Wufeng Formation and lower Longmaxi Formation (WF2-LM4 graptolite shale zones) has a strong sealing efficiency .…”
Section: Characteristics Of Overpressured and Normally Pressured Shal...mentioning
confidence: 99%
“…The regional caprocks are mainly composed of mudstone, shale, and gypsum-salt rocks. Notably, the Triassic gypsum-salt caprock plays an important role in maintaining the pressure system of the Wufeng–Longmaxi Formation shale gas reservoirs . However, the properties and sealing efficiency of the direct caprock portray variations in different regions.…”
Section: Characteristics Of Overpressured and Normally Pressured Shal...mentioning
confidence: 99%
See 1 more Smart Citation
“…The roof of the Wu-Long formation Member I shale is the gray-dark gray siltstone of Long Member II (10 ∌ 35 mm thick in the Jiaoshiba region) and the gray-dark gray mudstone of Long Member III (100 ∌ 140 mm thick in the Jiaoshiba region), and the average porosity, permeability, and breakthrough pressure of the two members mentioned above are respectively 2.4%, 0.0016 × 10 −3 ÎŒm 2 , and 69.8 ∌ 71.2 MPa (Borjigin et al, 2017;Dong et al, 2018). Meanwhile, the floor of the Wu-Long Formation Member I shale is the nodular limestone of the Lingxiang and Baota Formations (30 ∌ 40 mm thick in the Jiaoshiba region with average porosity of 1.58%), featuring a permeability of 0.0017 × 10 −3 ÎŒm 2 and a breakthrough pressure of 64.5 ∌ 70.4 MPa (Nie et al, 2019;Jin et al, 2020). The structural evolution simulation indicated that the gypsum rock on the top of JiaoYe1 well located at the higher part of the structure was destroyed (5 ∌ 0 Ma before the present which is relatively late), while the section of the well located at the lower part of the structure still preserves the gypsum rock stratum that is 70 ∌ 250 mm thick with porosity generally smaller than 2.00%, and breakthrough pressure generally over 60 MPa as well as excellent sealing performance.…”
Section: Sealing Of Shale Roof and Floormentioning
confidence: 99%
“…The characteristics of shale oil and gas occurrence and reservoir space figure prominently in the study of shale reservoir characteristics (He et al, 2019;He et al, 2020). Previous studies have been carried out on the characteristics of shale reservoirs (Gao et al, 2018;Jin et al, 2018;Gao et al, 2020;Jin et al, 2020;Li, 2022). To be specific, by virtue of rock thin section, SEM with Ar-ion milling, nuclear magnetic resonance (NMR), high-pressure mercury intrusion and lowtemperature nitrogen adsorption experiment, a study was conducted on the low maturity continental shale strata of Lower Sub-member 3-Upper Sub-member 4 in Paleogene Shahejie Formation, Dongying Sag.…”
Section: Introductionmentioning
confidence: 99%